Costos de la educación en Tucumán: El salario docente. Evolución y composición - Liliana Macián de Barbieri (Colegio de Economistas de A Coru\~na, 2008)
– This study shows that the average salary of teachers (in primary and secondary schools) in the province of Tucuman (Argentina) has not evolved uniformly in real terms in the period since the mid-1990s. Real salaries grew slowly between 1996 and 2001, declined significantly between 2002 and 2004, and then recovered starting in 2005. By March 2008, real salaries were significantly higher than during 2001-2003, as required by the Law of Financing for Education of 2005. The study also highlights the large dispersion in the level of salaries for the same position across provinces, as well as the large differences between basic and gross salaries in the various provinces. It also compares the salaries of teachers with those of other occupations in the same region.
Keywords: 330; education; teacher's salaries